Effect of particle strength on the monotonic shear strength of clinker ash. Issue 3 (30th September 2013) - Nakashita, A.; Winter, M.; Nakata, Y.; Ohara, N.; Yoshimoto, N.; Hyodo, M.; Yoshioka, I.
Abstract : Particle crushing tests were performed on single particles from six types of clinker ash, as well as a series of monotonic shear tests using effective confining pressures σ ′ c of 50, 100 and 200 kPa at an intended degree of compaction D c = 100%, in order to investigate the relationship between particle strength and monotonic shear strength. Samples with intended degrees of compaction D c = 85% and 90% were also tested at σ ′ c = 50 and 100 kPa in order to investigate the effect of degree of compaction on the shear strength of clinker ash. It was found that clinker ash is a crushable material with weak particle strength when compared with natural sands, although it has higher shear strength especially at D c ≥ 95%, where the shear resistance angle exceeds 45°. The average crushing stress σf of the particles shows a strong correlation with the residual secant friction angle φres, with φres increasing along with the average crushing stress σf . It was also found that σf can be used to calculate φres and, in turn, the peak secant friction angle φpeak of clinker ash.